Diminishing or Vanishing Cultures in Sri Lanka. - Subathini, R. (University of Kelaniya, 2013)
Sri Lanka is a country with the greatest linguistic diversity in the world. It can be considered as the largest pool of various cultures enriched with Buddhism, Hinduism Islam and Christianity. To preserve these cultures one must understand their current social standing, the economic situation, problems that they are faced with, values and skills they have preserved with. Changing culture and diminishing culture are two things, but the present change disregard and eliminate long standing traditions. Why do people talk about preserving these cultures, for what, for whose benefit? Already changed society is of the opinion that the cultures of ethnic groups are interesting and important.
Keywords: Diminishing; Vanishing; Cultures; Globalization; Sri Lanka